Teaching Students to Negotiate Like a Lawyer - John Lande (Washington University Journal of Law & Policy, 2012)
This Essay is intended to help instructors plan and teach negotiation courses, recognizing that every course should be tailored to fit the interests, capabilities, resources, and constraints of the instructors and students. Some of the ideas in this Essay will not work well in particular courses and even I did not incorporate them all. Although these suggestions are specifically designed for law school courses, instructors teaching in other contexts may get some helpful ideas for their courses as well. Part II of this Essay describes how lawyers negotiate in practice and lists a variety of negotiations that lawyers regularly engage in. Part III identifies some problems with the contemporary use of negotiation simulations, which are central components of most negotiation courses. Part IV suggests ideas for overcoming these problems. The main suggestion is to use multi-stage simulations in addition to single-stage simulations. Part IV also discusses debriefing of simulations and other elements in negotiation courses.
Keywords: Lawyering; Negotiation; Legal education – innovative approaches; The Carnegie Report; Role-play; Law schools – courses; Teaching methods; Maximal-result; concessions-oriented (MRCO); Appropriate-result; consensus-oriented (ARCO); Law students